2009
DOI: 10.1371/journal.pone.0006453
|View full text |Cite
|
Sign up to set email alerts
|

5-Hydroxytryptamine Modulates Migration, Cytokine and Chemokine Release and T-Cell Priming Capacity of Dendritic Cells In Vitro and In Vivo

Abstract: Beside its well described role in the central and peripheral nervous system 5-hydroxytryptamine (5-HT), commonly known as serotonin, is also a potent immuno-modulator. Serotoninergic receptors (5-HTR) are expressed by a broad range of inflammatory cell types, including dendritic cells (DCs). In this study, we aimed to further characterize the immuno-biological properties of serotoninergic receptors on human monocyte-derived DCs. 5-HT was able to induce oriented migration in immature but not in LPS-matured DCs … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
108
0
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 144 publications
(116 citation statements)
references
References 46 publications
(64 reference statements)
6
108
0
2
Order By: Relevance
“…Because 5-HT 7 receptor expression has been shown to be more prominent on mature DCs (34), it can be reasoned that 5-HT-induced modulation of cytokine release is dependent on the differentiation stage of DCs, and 5-HT 7 receptormediated influence on cytokine secretion is maturation dependent. Similar effects of 5-HT on cytokine secretion have been observed in monocyte-derived DCs (70). We found that addition of LPS to CD11c + colonic DC culture did not significantly upregulate IL-12p40, IL-6, and TNF-a with or without 5-HT stimulation.…”
Section: Cd11csupporting
confidence: 84%
“…Because 5-HT 7 receptor expression has been shown to be more prominent on mature DCs (34), it can be reasoned that 5-HT-induced modulation of cytokine release is dependent on the differentiation stage of DCs, and 5-HT 7 receptormediated influence on cytokine secretion is maturation dependent. Similar effects of 5-HT on cytokine secretion have been observed in monocyte-derived DCs (70). We found that addition of LPS to CD11c + colonic DC culture did not significantly upregulate IL-12p40, IL-6, and TNF-a with or without 5-HT stimulation.…”
Section: Cd11csupporting
confidence: 84%
“…Serotonin directly modulates functions of several other immune cells, but unlike in the case of dendritic cells, mast cells, and eosinophils, serotonin did not act as a chemoattractant to induce in vitro migration of neutrophils. 7,[41][42][43][44] In vitro plateletneutrophil rosetting was also independent of the platelet serotonin content, indicating that serotonin does not influence platelet P-selectin expression and platelet-neutrophil interactions. It is more probable that serotonin enhances neutrophil extravasation by regulating endothelial selectin expression, because serotonin induces WPB exocytosis in cultured endothelial cells 10,11 and injection of serotonin enhanced leukocyte rolling in the Tph1 Ϫ/Ϫ mice.…”
Section: Discussionmentioning
confidence: 95%
“…Human monocytes release different cytokines and chemokines, mainly via 5-HT 3 , 5-HT 4 and 5-HT 7 activation (35). Past studies also showed that 5-HT increase production of the pro-inflammatory cytokine IL-6 in mature Dendritic cells (DCs) via 5-HT 3 , 5-HT 4 and 5-HT 7 (8,9). And DCs are known to produce different chemokines thereby regulating the traffic of Th1 and Th2 cells into inflamed tissue (36).…”
Section: Discussionmentioning
confidence: 99%
“…More than 90% of 5-HT in the body is secreted from EC cells which are located within the mucosal mucosa, and the tryptophan hydroxylase (TPH) which in EC cells is the rate-limiting enzyme in the 5-HT synthesis process (5)(6)(7). Moreover, recent studies indicated that CD4 + T cells played an important role in the development of colonic EC cell hyperplasia in intestinal infection, and EC cells were influenced by helper T-cell subtype 1 (Th1) or subtype 2 (Th2) cytokine predominant environments (8,9). Cynaropicrin ( Fig.…”
Section: Introductionmentioning
confidence: 99%